2004
DOI: 10.1111/j.1600-0668.2004.00281.x
|View full text |Cite
|
Sign up to set email alerts
|

Productivity and fatigue

Abstract: This paper introduces interesting new methods for evaluation of people's fatigue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 4 publications
(5 reference statements)
3
41
0
1
Order By: Relevance
“…Tanabe et al [6] tested the effect of moderately hot environments at 25 C, 28 C, and 33 C on office work performance via a subjective experiment. The effect differed between task types and was inconsistent, while there was a clear trend of greater mental fatigue with higher temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Tanabe et al [6] tested the effect of moderately hot environments at 25 C, 28 C, and 33 C on office work performance via a subjective experiment. The effect differed between task types and was inconsistent, while there was a clear trend of greater mental fatigue with higher temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Early research in the …eld of Ergonomics (Cakir et al 1980) has shown that as fatigue rises, productivity falls. Tanabe and Nishihara (2004) use lab experiments to study changes in productivity and …nd that even though people are highly motivated in short term experiments, they become tired and performance deteriorates over a longer time frame as fatigue kicks in. Likewise, a key …nding in the studies by Caldwell (2001) andSetyawati (1995) is that fatigued workers exhibit diminished productivity.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Indoor air temperature has a significant effect on employees' work efficiency, productivity, motivation, comfort and health (Tanabe and Nishihara, 2004;Kekäläinen et al, 2010;Lan et al, 2010). Thus, adjusting and maintaining air temperature in the comfort zone (21 -238C) is vital to improving these parameters (Tanabe and Nishihara, 2004;Kekäläinen et al, 2010;Lan et al, 2010).…”
Section: Designing Architecture For An Intelligent Work Environmentmentioning
confidence: 95%
“…Thus, adjusting and maintaining air temperature in the comfort zone (21 -238C) is vital to improving these parameters (Tanabe and Nishihara, 2004;Kekäläinen et al, 2010;Lan et al, 2010). Studies by Niemelä et al have shown that worker productivity may fall by 5-7 per cent at elevated indoor temperatures (Niemelä et al, 2002).…”
Section: Designing Architecture For An Intelligent Work Environmentmentioning
confidence: 96%
See 1 more Smart Citation